Pengaruh Kepuasan Kerja Terhadap Komitmen Organisasi Karyawan PT. Angkasa Pura 1 Bandar Udara Internasional El Tari Kupang Nusa Tenggara Timur - Julianti Hendrika Wowa; Desiana Rachmawati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Organizattional commitment an organization will be said to be successful or not in achieving its goals determined by employee satisfaction. Jib satisfaction can affect several types,namely the type of work itself, salary or pay, opportunities for promotion, relationships with superiors and comworkers can be fulfilled properly, so that satisfaction will have an impact on organizational commitment. The purpose of this study is to determine the effect and magnitude of job satisfaction on employee organizational commitment. In this study, researchers used quantitative methods using primary data, which was carried out by distributing questionnaires online to 33 employees of PT. ANGKASA PURA 1 El Tari Kupang Airport. The data were then processed using simple linear regression. The result of this study indicate that the simple linear regression test shows a significant value of 0,000 < 0,005 which states that H0 is rejected and Ha is accepted. From these result it was concluded that job satisfaction affects employee organizational commitment where job satisfaction increases, organizational commitment will increase.